2014
DOI: 10.1371/journal.pone.0099585
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Laponite Bioceramics for Potential Bone Tissue Engineering Applications

Abstract: We report a facile approach to preparing laponite (LAP) bioceramics via sintering LAP powder compacts for bone tissue engineering applications. The sintering behavior and mechanical properties of LAP compacts under different temperatures, heating rates, and soaking times were investigated. We show that LAP bioceramic with a smooth and porous surface can be formed at 800°C with a heating rate of 5°C/h for 6 h under air. The formed LAP bioceramic was systematically characterized via different methods. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…LAP is silicate, thus the mechanism of apatite mineralization on the composites scaffolds might be similar to the apatite mineralization on silicate-based biomaterials in SBF (rich Si-OH rst formed on material surface in SBF, then induced Ca ion distribution, calcium phosphate nucleation, and ultimate apatite formation) as described in previous publications. 5 Cells adhesion and spreading on the biomaterial surface are the rst sequential reactions, which are crucial for subsequent cells proliferation and differentiation. 34 In this study, from the SEM micrographs, the MC3T3-E1 cells adhered and spread better on sPL30 than sPL15, and sPL15 better than sPL0 scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAP is silicate, thus the mechanism of apatite mineralization on the composites scaffolds might be similar to the apatite mineralization on silicate-based biomaterials in SBF (rich Si-OH rst formed on material surface in SBF, then induced Ca ion distribution, calcium phosphate nucleation, and ultimate apatite formation) as described in previous publications. 5 Cells adhesion and spreading on the biomaterial surface are the rst sequential reactions, which are crucial for subsequent cells proliferation and differentiation. 34 In this study, from the SEM micrographs, the MC3T3-E1 cells adhered and spread better on sPL30 than sPL15, and sPL15 better than sPL0 scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…3 Study has shown that LAP induced the osteogenic differentiation of the MC3T3-E1 cells by enhancing ALP activity, runt-related transcription factor 2 (RUNX2) transcript upregulation, bonerelated matrix protein deposition (osteocalcin and osteopontin), following by matrix mineralization. 4,5 In previous studies, LAP has been incorporated into electrospun poly(lactic-co-glycolic acid) nanobers scaffolds, which remarkably enhanced osteoblastic differentiation (alkaline phosphatase activity and osteocalcin secretion) of human mesenchymal stem cells (hMSCs). 3,6 In addition, nanocomposite hydrogel of cross-linked poly(ethylene oxide) and LAP with the content ranging from 40 to 70 wt% were prepared, which signicantly stimulated the adhesion, spreading, proliferation and differentiation of the MC3T3-E1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the disadvantages of tissue-based bone graft, synthetic biocompatible scaffolds have been applied in tissue engineering for bone regeneration. [3][4][5] Hydroxyapatite (HAP; Ca 10 (PO 4 ) 6 (OH) 2 ), a major inorganic component of biological hard tissues such as bone and tooth, has been widely investigated for its application in bone tissue engineering owing to its excellent biocompatibility and biodegradability. [6][7][8][9] For example, Bhumiratana et al 10 explored the incorporation of silk sponge matrices with HAP microparticles to generate highly osteogenic composite scaffolds, which could induce in vitro bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Despite advances in the physical and chemical properties of polymers by reinforcement with nanoclay, few studies have examined the interaction between clay-based scaffolds and cells. [23][24][25][26] Ambre et al reported that incorporating synthetic silicate into chitosan/polygalacturonic acid scaffolds promoted osteogenic differentiation of human mesenchymal stem cells (hMSCs). 26 Hong Zhuang et al found out that montmorillonite-intercalated gelatin/chitosan induced the adhesion and proliferation of rat stromal stem cells; 27 Ganesh Nitya et al demonstrated hMSCs seeded on scaffolds embedded with halloysite nanoclay showed higher proliferation rate and alkaline phosphatase (ALP) activity.…”
Section: Introductionmentioning
confidence: 99%